Behavioral and binding studies on the quinolinyl ester indoles 5F-PB22 (5F-QUPIC) and BB-22 (QUCHIC) in the mouse model. (2022) - Corli, Giorgia; Tirri, Micaela; Arfè, Raffaella; Bilel, Sabrine; Marchetti, Beatrice; Gregori, Adolfo; Di Rosa, Fabiana; Vincenzi, Fabrizio; De-Giorgio, Fabio; Borea, Pier Andrea; Varani, Katia; Marti, Matteo
Abstract: Novel Psychoactive Substances newly introduced on the drug market are constantly changing patterns of drug consumption. Among these, Synthetic Cannabinoids (SCs) mainly dominated European seizures in the last years. Quinolin-8-yl 1-(5-fluoropentyl)-1H-indole-3-carboxylate (5F-PB22) and quinolin-8-yl 1-(cyclohexylmethyl)-1H-indole-3-carboxylate (BB-22) are SCs whose abuse has been linked to a range of fatal intoxications and hospitalizations. Therefore, this study aims to investigate and compare in vitro and in vivo pharmacodynamics activity of these quinolinyl ester indoles. In vitro competition binding experiments performed on CD-1 murine and human cannabinoid CB1 and CB2 receptors revealed a sub-nanomolar affinity and potency of 5F-PB22 and BB-22. In vivo studies demonstrated that the acute systemic administration of 5F-PB22 and BB-22 (0.001-6 mg/kg) deeply impaired sensorimotor and motor responses, core temperature, breath rate and nociceptive threshold of CD-1 male mice. Pre-treatment with the selective cannabinoid CB1 receptor antagonist/inverse agonist AM-251 (6 mg/kg) fully prevented the effects of both cannabinoids (at 1 mg/kg) suggesting a CB1 receptor mediated action. Relying on these findings, this study showed for the first time the pharmaco-toxicological effects of these substances confirming their potential burden on human health. Furthermore, it revealed that the difference of the chemical structures of the two SCs results in their potency related disparities.